Factors Affecting Women's Autonomous Decision Making In Research Participation Amongst Yoruba Women Of Western Nigeria. Issue 1 (12th February 2016) - Princewill, Chitu Womehoma; Jegede, Ayodele S.; Nordström, Karin; Lanre‐Abass, Bolatito; Elger, Bernice Simone
Abstract: Research is a global enterprise requiring participation of both genders for generalizable knowledge; advancement of science and evidence based medical treatment. Participation of women in research is necessary to reduce the current bias that most empirical evidence is obtained from studies with men to inform health care and related policy interventions. Various factors are assumed to limit autonomy amongst the Yoruba women of western Nigeria. This paper seeks to explore the experience and understanding of autonomy by the Yoruba women in relation to research participation. Focus is on factors that affect women's autonomous decision making in research participation. An exploratory qualitative approach comprising four focus group discussions, 42 in‐depth interviews and 14 key informant interviews was used. The study permits a significant amount of triangulation, as opinions of husbands and religious leaders are also explored. Interviews and discussions were audiotaped and transcribed verbatim. Content analysis was employed for data analysis. Findings show that concepts of autonomy varied amongst the Yoruba women. Patriarchy, religion and culture are conceived to have negative impact on the autonomy of women in respect to research participation. Among the important findings are: 1) male dominance is strongly emphasized by religious leaders who should teach equality, 2) while men feel that by making decisions for women, they are protecting them, the women on the other hand see this protection as a way of limiting their autonomy. We recommend further studies to develop culturally appropriate and workable recruitment methods to increase women's participation in research.